IDENTIFIKASI LARVA LALAT PADA BANGKAI HAMSTER SYRIA (Mesocricetus auratus Waterhause) DENGAN EUTHANASIA DISLOKASI, DIRACUN DAN DIBAKAR - Ichsan Luqmana Indra Putra; Tri Liana Marthadella (Fakultas MIPA Universitas Negeri Gorontalo, 2021)
Flies are the most commonly used insects in forensic entomology, namely as an indicator for determining the duration of death or PMI (Post Mortem Interval). The flies that usually come first and colonize carcasses are the Muscidae, Sarcophagidae, and Calliphoridae families. The purpose of this study was to determine the species of flies found in the carcass of Syrian Hamster (Mesocricetus auratus Waterhause) with different euthanasia outdoors, and to see which types of flies were abundant and not abundant in each treatment. The research was conducted in Bedoyo Village, Ponjong, Gunung Kidul, Yogyakarta Special Region, from September to March. The sample consisted of 9 male Syrian Hamsters (M. auratus) divided into 3 groups of euthanasia, namely dislocation by pulling the body and neck, burning on firewood for 30 seconds, and poisoning with 2.5 ml of liquid mosquito repellent. The hamster carcass was then placed on the ground covering an area of 504 m2 with a distance between the carcasses of 2.5 m. The collection of fly larvae is carried out every 2 days for 6 days or until the carcass is decomposed. Data analysis was performed using descriptive analysis to describe the types of flies found in hamster carcasses and inferential to calculate the correlation between abiotic factors and the abundance of fly larvae in the three treatments. The fly species found were Chrysomya megachepala in euthanasia dislocation 1 larvae and Sarcophaga haemorrhoidalis in euthanasia dislocation 14, poisoned 16 and burned 25 larvae. The presence and abundance of C. megacephala and S. haemorrhoidalis in carcasses did not correlate with the measured abiotics. The conclusion of this study is the type of treatment can affect the type and abundance of flies found on the carcass.